Field notes contributed by Dennis L. Carter, July 31, 2003 - Carter, Dennis L.et al (2003)
List of birds and locations contributed by Dennis L. Carter with observers Larry Reis and Ellen Bell. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2003. Epson - sheet feed